Growth performance of weaner pigs fed diets containing grains milled to different particle sizes. I. Sorghum - Nguyen, G. T.; Collins, C.; Henman, D.; Diffey, Simon; Tredea, A. M.; Black, J. L.; Bryden, W.; Gidley, M. J.; Sopade, P. A. (2015)
Sorghum is the third most important cereal in Australia, in terms of production, and it is a major feed grain (Mahasukhonthachat et al. 2010). Mahasukhonthachat et al. (2010) and recently, Nguyen et al. (2015), revealed particle size and mill type as the primary determinants of in-vitro digestion properties of grains. However, there are limited studies on the effects of grain particle size and mill type on animal performance. Using sorghum, this study investigated these effects on performance of weaner pigs, and tested the hypothesis that within an optimum particle size range, pig performance is not affected. Sorghum (var. MR43) was milled with industrial-scale hammer (HM) and disc (DM) mills, in a randomised experiment with two replicates. Four screens (2, 3, 4, and 5mm)and four disc gaps were used in theHMandDMrespectively. Four additional treatments were obtained by mixing the finest (F) and coarsest (VC) sizes from the mills (HMF-DMF,HMF-DM VC,HMVC-DMF, andHMVC-DM VC). Experimental diets [15 MJ digestible energy (DE)/kg, 1 g available lysine/MJ DE, 220 g/kg crude protein, and 350 g/kg starch), consisting 49.8% of the milled sorghum, were fed ad libitum to weaner pigs for 21 d.Atotal of 289 weaner pigs (Large White · Landrace, PrimeGro Genetics) aged 28 days and having a bodyweight of 6.8 0.1 kg (mean SD), were individually housed and used in three batches in a randomised block design, with some incomplete blocks. There were 20 diets from the 12 particle size treatments, and 24 pigs were used per treatment. Pigs and feed residues were weighed weekly to calculate average daily feed intake (ADFI), average daily gain (ADG)and feed conversion ratio (FCR). The Rivalea animal ethics committee approved (14N009) the animal experiment. The diets were analysed (Nguyen et al. 2015) for geometric mean particle size diameter (Dgw) and geometric standard deviation of mean particle diameter (Sgw). Statistical methods (ASReml-R) analogous to ANOVA were used (Butler 2009). TheDgw of the milled sorghum ranged from 400–800mm, with up to50%of the particles being higher than 1000mmin size. There was no pronounced (P> 0.05) mill effect on Sgw, and neither the mill nor particle size affected (P> 0.05) the pig growth (Table 1). Irrespective of the mill or particle size, the pigs consumed (ADFI) and grew (ADG) more with age (not shown). The Dgw of the diets (600–750 mm) was not significantly different (P > 0.05) from that of the milled sorghum, and, therefore, the ingredients did not influence theDgw of the diets. Hence, the measured animal responses were mainly due to the particle size of the milled sorghum. The absence of significant mill and particle size effects suggests 400–800 mm as the optimum particle size range for sorghum fed to weaner pigs. Feed mills, therefore, need not grind sorghum below 400 mm for milling economy, and particle size above 800 mm might be undesirable for good performance of weaner pigs fed sorghum-based diets.